2016
DOI: 10.1038/srep32671
|View full text |Cite
|
Sign up to set email alerts
|

Visualising phase change in a brushite-based calcium phosphate ceramic

Abstract: The resorption of brushite-based bone cements has been shown to be highly unpredictable, with strong dependence on a number of conditions. One of the major factors is phase transformation, with change to more stable phases such as hydroxyapatite affecting the rate of resorption. Despite its importance, the analysis of phase transformation has been largely undertaken using methods that only detect crystalline composition and give no information on the spatial distribution of the phases. In this study confocal R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 39 publications
2
23
0
Order By: Relevance
“…The weak band at 1003 cm −1 observed in the B (Figure b, red line) and C syntheses (Figure b, blue line) corresponds to the monohydrogen phosphate (HPO 4 2− ) and it can be due to the type of reagents used for the different syntheses (disodium hydrogen phosphate for Synthesis B and diammonium hydrogen phosphate for Synthesis C) or also due to the presence of other calcium phosphate subproducts such as octacalcium phosphate (OCP; Bannerman, Williams, Cox, & Grover, ).…”
Section: Resultsmentioning
confidence: 99%
“…The weak band at 1003 cm −1 observed in the B (Figure b, red line) and C syntheses (Figure b, blue line) corresponds to the monohydrogen phosphate (HPO 4 2− ) and it can be due to the type of reagents used for the different syntheses (disodium hydrogen phosphate for Synthesis B and diammonium hydrogen phosphate for Synthesis C) or also due to the presence of other calcium phosphate subproducts such as octacalcium phosphate (OCP; Bannerman, Williams, Cox, & Grover, ).…”
Section: Resultsmentioning
confidence: 99%
“…Perhaps because HA compositionally resembles the mineral component of bone, the majority of CPC research initially focused on the formulation and refinement of HA‐based cements. Researchers have, however, demonstrated that highly crystalline HA is poorly soluble in physiological conditions and is therefore only resorbed by osteoclastic activity . This means HA cements can remain in vivo for a considerable period of time following implantation, posing a risk of catastrophic brittle failure .…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have, however, demonstrated that highly crystalline HA is poorly soluble in physiological conditions and is therefore only resorbed by osteoclastic activity. [13][14][15] This means HA cements can remain in vivo for a considerable period of time following implantation, posing a risk of catastrophic brittle failure. 2 More soluble apatites, however, can be produced by reducing crystal size or crystallinity and incorporating substitutions (eg Mg 2+ , CO 3 2À ) into the apatite lattice.…”
Section: Introductionmentioning
confidence: 99%
“…The results are shown in FIGURE 2, as a function of (NH 2 ) 2 CO concentration. When the (NH 2 ) 2 CO concentrations were 0.04 and 0.08 mol•dm 3 , CaHPO 4 and OCP Relating to the formations of CaHPO 4 and OCP, the former compound is stable for pH < 4 25 . On the other hand, the latter compound is favored as a metastable phase in the range of pH ≃ 4 to pH ≃ 6.5, although the non-stoichiometric HAp (i.e.,Ca 10x (HPO 4 ) x (PO 4 ) 6-x (OH) 2x ) is also thermosdynamically stable for pH > 4 25 .…”
Section: Preparation Of Fibrous Ocp/hap Particlesmentioning
confidence: 99%